2023
DOI: 10.1093/europace/euad041
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive three-dimensional electrical activation mapping to predict cardiac resynchronization therapy response: site of latest left ventricular activation relative to pacing site

Abstract: Aims Pacing remote from the latest electrically activated site (LEAS) in the left ventricle (LV) may diminish response to cardiac resynchronization therapy (CRT). We tested whether proximity of LV pacing site (LVPS) to LEAS, determined by non-invasive three-dimensional electrical activation mapping [electrocardiographic Imaging (ECGI)], increased likelihood of CRT response. Methods and results Consecutive CRT patients underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…recently showed that non-invasive three-dimensional electrical activation mapping to assess the QLV was a strong predictor for CRT response. 34 In the substudy of ImagingCRT however, QLV was not able to discriminate between CRT responders and non-responders. 35 Instead, a longer inter-electrical delay of ≥100 ms was found to be independently associated with more pronounced LV reverse remodelling after 6 months of follow-up, 35 and was associated with reduced all-cause death and HF hospitalization during long-term follow-up.…”
Section: Discussionmentioning
confidence: 97%
“…recently showed that non-invasive three-dimensional electrical activation mapping to assess the QLV was a strong predictor for CRT response. 34 In the substudy of ImagingCRT however, QLV was not able to discriminate between CRT responders and non-responders. 35 Instead, a longer inter-electrical delay of ≥100 ms was found to be independently associated with more pronounced LV reverse remodelling after 6 months of follow-up, 35 and was associated with reduced all-cause death and HF hospitalization during long-term follow-up.…”
Section: Discussionmentioning
confidence: 97%
“…Alternative approaches to determine the optimal LV lead position have been proposed, using either electrical or image-based guidance. 18 , 19 While less invasive, these methods rely on indirect mechanisms to provide feedback, rather than evaluate actual changes in LV performance. Therefore, such methods may be less suitable to evaluate device programming or perioperatively compare the effects of different pacing modalities, as is the case when comparing BVP and conduction system pacing.…”
Section: Discussionmentioning
confidence: 99%
“…Quadripolar leads allow for more choices regarding pacing sites regardless of positioning, including ability to pace from nonapical sites despite apical lead placement 9 Compared to anatomic locations, placement of LV leads in areas of electrical delay can confer a greater benefit 262 . In a post hoc analysis of a large multicenter RCT, 252 HF clinical composite outcomes were assessed relative to interventricular electrical delay (short delay being <67 ms and long delay being ≥67 ms) in patients who underwent CRT placement.…”
Section: Section 5 Implant Proceduresmentioning
confidence: 99%
“…9 Compared to anatomic locations, placement of LV leads in areas of electrical delay can confer a greater benefit. 262 In a post hoc analysis of a large multicenter RCT, 252 HF clinical composite outcomes were assessed relative to interventricular electrical delay (short delay being <67 ms and long delay being ≥67 ms) in patients who underwent CRT placement. The long interventricular electrical delay group had more clinical improvement, less clinical deterioration, and higher freedom from HFH or mortality.…”
Section: Section 5 Implant Proceduresmentioning
confidence: 99%